Ответы и объяснения

2014-02-26T16:21:05+04:00
Нужно приравнять числитель и знаменатель к 0
2a^2+5a-3=0                                       a^2+a-6=0
D=25+24=49                                       по т.Виета: 
a1=(-5+7)/2=1/2                                  a1*a2=-6
a2=(-5-7)/2=-3                                     a1+a2=-1; a1=-3 a2=2
по формуле получается:                    
2(a-1/2)(a+3)                                      (a+3)(a-2)
записываем в виде дроби: (2a-1)(a+3)/(a+3)(a-2)=(2a-1)/(a-2)